INDIGENOUS HUNTING IN INDONESIAN NEW GUINEA: CULTURAL IDENTITY, FOOD SECURITY AND INCOME OPPORTUNITIES - Agustina Y S Arobaya; Deny A Iyai; Johan F Koibur; Martha Kayadoe; Freddy Pattiselanno (Media Konservasi, 2021)
Wildlife hunting is important in satisfying people’s need for meat as a source of dietary protein as well as being of economic value to the studied communities. Many people in Indonesian New Guinea rely on the benefits obtained from the extraction of plants and animals in the tropical forests, including hunting. This review aims to synthesise existing knowledge and identify areas that are fundamental to the body of knowledge on Indigenous hunting that has been integrated into many forest people societies in Indonesian New Guinea. People keep a relationship with nature by harmonising Indigenous hunting and cultural background. Available food source from wildlife and limited access to livestock were the major reason to acquire wild animals for consumption through hunting. Throughout of Indonesian New Guinea, the commercial hunting provide more opportunities for income generation. Indigenous hunting has long been part of cultural life of forest, providing a source of dietary protein to the household, and offer forms of income generation to the studied communities. Key words: Culture, Food consumption, trade, Indigenous hunting, Indonesian New Guinea